A multi-temporal remote sensing approach for monitoring changes in spatial extent of freshwater lake of Deepor Beel Ramsar Site, a major wetland of Assam (Journal of Wetlands Ecology, 2011)
Sustainability of wetland ecosystem is necessary for various important functions such as food storage, water quality continuation and providing habitat for different species of flora and fauna. Hence, an inventory of wetlands of any region is a pre-requisite for their conservation and management. This study has been carried out to delineate the change in freshwater lake of ‘Deepor Beel’ wetland of Assam, India, using LANDSAT TM data. Field observation shows that the ecosystem is facing both natural as well as anthropogenic threats. Rapid urbanization, Illegal settlements, industries, invasive species (Eichhornia crassipes) are the major cause of this wetland decline. It has been found that massive decline occurred between the period 1991 to 2001 i.e., 1.891 sq.km which was at the rate of -0.171 per year where as the decline between the period 2001 to 2010 was found to be 1.013 sq. km which was at a rate of -0.101. The total area of open water bodies has decreased by 2.904 sq. km from 1991 to 2010 i.e. 59.19%. Thus the overall rate of change in the water bodies from 1991 to 2010 to other land use categories was found to be -0.145. Hence the study reveals the potentiality of Landsat TM data mapping the change in the wetland ecosystem. It is further hoped that the study will have high utility in preparing management plan for conservation of this ecosystem. Keywords: Wetland; Landsat TM; Thresholding; density sliceDOI: http://dx.doi.org/10.3126/jowe.v5i0.4696 J Wet Eco 2011 (5): 40-47